Assessment of lipid peroxidation and total antioxidant capacity in patients with breast cancer - Abdullatif Taha Babakr; Mohamed Mahmoud Nour Eldein (Exploration of Targeted Anti-tumor Therapy)
Aim: Breast cancer (BC), a disease in which abnormal breast cells grow out of control and form tumors, is a prevalent life-threatening disease worldwide. Oxidative stress has been implicated in the development and progression of various cancers, including BC. Assessing lipid peroxidation and overall antioxidant status in BC offers valuable information on disease progression, patient prognosis, and the effectiveness of therapeutic options. Methods: A total of 150 women were categorized into three groups: normal, benign mass, and BC. Participants were selected and evaluated at the cancer clinic; fasting blood samples were collected, and total antioxidant capacity (TAC), oxidized low-density lipoprotein (Ox-LDL), cancer antigen (CA) 15-3, and carcinoembryonic antigen (CEA) were measured. Subsequently, statistical analysis was performed to compare the levels of these parameters in different groups and examine the analytical performance of TAC and Ox-LDL in BC. Results: In patients with malignancy, the serum level of TAC was significantly decreased compared with the benign group (8.3 U/mL and 16.04 U/mL, respectively) (P < 0.001). Healthy controls exhibited higher levels of TAC (43.4 U/mL). The levels of Ox-LDL in BC were significantly increased in both malignant and benign groups (3,831 pg/mL and 1,234 pg/mL, respectively) compared with normal controls (682 pg/mL) (P < 0.001). CEA and CA15-3 were drastically increased in the BC groups compared with the control group. A significant area under the curve was observed in the receiver operating characteristic (ROC) curve analysis for TAC (0.975, P < 0.001) and Ox-LDL (0.986, P < 0.001). Conclusions: This study revealed that patients with BC had lower TAC and higher Ox-LDL serum levels, indicating elevated oxidative stress. These levels may serve as promising monitoring parameters in BC.